Persistence and genetic vulnerability of tropical tree species in response to anthropogenic disturbances - Kanchanarak, Tania (2024)
Tropical forests face numerous threats, including overexploitation, selective logging, and fragmentation arising from landscape changes. These disturbances reduce tree population density and increase distances between individuals, altering their reproductive behaviour. Decreased numbers of mature trees and disrupted gene flow reduce reproductive success and genetic diversity, potentially leading to inbreeding, genetic drift, or even extinction. Consequently, landscape restoration techniques became a global priority. Tropical trees are long-lived organisms, and there is a significant knowledge gap regarding their long-term survival in the context of anthropogenic disturbances and restoration. This thesis aims to contribute to the conservation and restoration of tropical tree species using a mixed-methods approach, encompassing meta-analysis, simulation modelling, and survival analysis. All chapters focus on species from the ecologically and economically important tree family Dipterocarpaceae. Many species possess winged fruits, which disperse by wind and gyration, and they generally reproduce during supra-annual masting flowering events. It has been hypothesised that trees respond differently to disturbances based on traits like flower size and wood density. The first chapter provides a general introduction to the topics addressed in this thesis and outlines the existing knowledge gaps. It gives an overview of the impacts of anthropogenic disturbances and restoration efforts on trees and highlights the importance of modelling in understanding and predicting the effects of various landscape uses on trees. In Chapter 2, I conducted a literature and data synthesis to investigate how fragmentation and logging impacted 277 adult and offspring populations of 45 dipterocarp species. I extracted data on three different genetic metrics to examine how genetic vulnerability was affected by anthropogenic disturbance and test whether genetic vulnerability was differentially explained by the traits of flower size, fruit size and wood density. Through a meta-analysis using phylogenetic linear mixed models, I found that genetic diversity of adult populations was significantly lower in fragmented and in forests with combined disturbances, while juvenile populations were generally unaffected. Additionally, I found a negative relationships between fruit size and genetic diversity as well as wood density on inbreeding in adult populations. While flower size and fruit size positively correlate to both genetic diversity and inbreeding in offspring populations. These results suggest that these traits could serve as useful surrogates for assessing genetic vulnerability despite the limited data on offspring populations.